Geometric knowledge and scientific rigor of digital photography: the case of nodal photography - Carpiceci, Marco (DISEGNARECON, 2013)
In the past the formation of the photographic image was almost exclusively delegated to a process of shooting, developing and printing or projecting. Today the picture has so many possibilities that it is difficult to delineate a clear and focused operative boundary. In digital photography, every step offers the opportunity of transformation. However the multiple possibilities offered by digital photography implya required knowledge of all those activities in which the automatisms can prevent user from the realization processes control. As emblem of general cognitive problem, we analyze a significant application field that we define “nodal photography”. It is based on a technique produced from the development of electronics and computer, and that encompasses many aspects of technological innovation we are experiencing.